Electoral laws and the 2007 general elections in Nigeria (2007)
Credible elections are a salient indicator of democratic consolidation and the principal institutionalised means of forming and changing democratic governments. A central determinant of the success of any election is the institutions which structure the behaviour of participants and the choices available to them, hence their belief in pay-offs to individuals and groups. The guiding principles and regulations of the 2007 general elections in Nigeria are to be found in the 1999 Constitution and in the Electoral Act 2006. These documents not only set out the rules, the enactment of the Electoral Act usually signals the beginning of the electoral contest. The Constitution and the Act together make elaborate provision for voter registration, party and candidate registration, campaign financing and regulation, election observation, ballot design, polling stations, voting, counting, and tabulation, election management bodies, and dispute settlement authorities. This paper reviews critically the constitutional provisions on elections and the Electoral Act 2006 in the context of the challenges of achieving credible elections in Nigeria.